EVALUATION OF THE 3R (REDUCE, REUSE, RECYCLE) WASTE DISPOSAL SITE PROGRAM IN THE CONTEXT OF REDUCING WASTE IN SUKABUMI CITY - May Widyastutie; Isman Kadar; Sri Wahyuni (Journal of Science Innovare, 2021)
Rapid population growth has had an impact on the environment, both positive and negative impacts in various fields, one of which is the waste problem which is still one of the national strategic issues. Waste management in Indonesia is regulated in Law Number 18 of 2008 concerning Waste Management and for the management of household waste or the like, it is operationally strengthened with the issuance of Presidential Regulation Number 97 of 2017 concerning National Policies and Strategies for the Management of Household Waste and Waste Similar to Household Waste. The 3R Garbage Disposal Program (reduce, reuse, recycle) is an alternative in processing household waste and similar household waste, where the main concept of waste processing in the 3R Disposal Site is to reduce the quantity and/or improve the characteristics of the waste to be disposed of. processed further at the Final Disposal Site. From 2009 to 2018, Sukabumi City has built 11 units of 3R Garbage Disposal with a processing capacity of 2 tons/day each spread over several villages in the Sukabumi City area, but only 9 3R Disposal Sites are still active. up to this moment. The purpose of this study is to analyze and describe the achievement or success of the 3R Waste Disposal Site program in the context of reducing waste in Sukabumi City. This study uses the CIPP method, which is an evaluation model on the Context, Input, Process and Product aspects. Data obtained from the results of document analysis, field observations and interviews. Based on the data analysis, it can be concluded that the 3R Waste Disposal Site program is feasible to be implemented as an effort to achieve the target of reducing household waste and similar household waste in accordance with regional policies and strategies in waste management. The Context aspect is categorized as good and can be the main basis for program implementation, the Input aspect is in sufficient category, the need for managerial Human Resources and technical Human Resources in the management of the 3R Waste Disposal Site and the fulfillment of maintenance costs to support the success of the program, the Process aspect is categorized as sufficient, needs optimization in the utilization of available facilities and infrastructure as well as innovation in building cooperation with the private sector for funding mechanisms, and the Product aspect is categorized as Good and still optimizing the performance of the 3R Waste Disposal Site management so that the 30% waste reduction target in 2025 can be achieved.